Transcription profile of Trichophyton rubrum conidia grown on keratin reveals the induction of an adhesin-like protein gene with a tandem repeat pattern. (December 2016) - Bitencourt, Tamires; Macedo, Claudia; Franco, Matheus; Assis, Amanda; Komoto, Tatiana; Stehling, Eliana; Beleboni, Rene; Malavazi, Iran; Marins, Mozart; Fachin, Ana
Abstract Background Trichophyton rubrum is a cosmopolitan filamentous fungus that can infect human keratinized tissue (skin, nails and, rarely, hair) and is the major agent of all chronic and recurrent dermatophytoses. The dermatophyte infection process is initiated through the release of arthroconidial adhesin, which binds to the host stratum corneum. The conidia then germinate, and fungal hyphae invade keratinized skin structures through the secretion of proteases. Although arthroconidia play a central role in pathogenesis, little is known about the dormancy and germination ofT. rubrum conidia and the initiation of infection. The objective of this study was to evaluate the transcriptional gene expression profile ofT. rubrum conidia during growth on keratin- or elastin-containing medium, mimicking superficial and deep dermatophytosis, respectively. Results A transcriptional profiling analysis was conducted using a custom oligonucleotide-based microarray by comparingT. rubrum conidia grown on elastin and keratin substrates. This comparison shows differences according to protein source used, but consisted of a very small set of genes, which could be attributed to the quiescent status of conidia. The modulated genes were related to the dormancy, survival and germination of conidia, including genes involved in the respiratory chain, signal transduction and lipid metabolism. However, an induction of a great number of proteases occurred whenT. rubrum was grown in the presence of keratin such as the subtilisin family of proteases (Sub 1 and Sub 3) and leucine aminopeptidase (Lap 1 and Lap 2). Interestingly, keratin also promoted the up-regulation of a gene encoding an adhesin-like protein with a tandem repeat sequence.In silico analysis showed that the protein contains a domain related to adhesin that may play a role in host-pathogen interactions. The expression of this adhesin-like gene was also induced during the co-culture ofT. rubrum with a human keratinocyte cell line, confirming its role in fungal-host interactions. Conclusion These results contribute to the discovery of new targets involved in the adhesion of conidia and the maintenance of conidial dormancy, which are essential for triggering the process of infection and the chronicity of dermatophytosis.